2016
DOI: 10.1111/adb.12484
|View full text |Cite
|
Sign up to set email alerts
|

Smokers and ex‐smokers have shared differences in the neural substrates for potential monetary gains and losses

Abstract: Abstract:Despite an increased understanding of nicotine addiction, there is a scarcity of research comparing the neural correlates of non-drug reward between smokers and ex-smokers. Long-term changes in reward-related brain functioning for non-drug incentives may elucidate patterns of functioning that potentially contribute to ongoing smoking behaviour in current smokers. Similarly, examining the effects of previous chronic nicotine exposure during a period of extended abstinence may reveal whether there are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Nevertheless, the group differences in smoking may have influenced our results. That is, similarly to alcohol, smoking a cigarette increases dopamine release in the midbrain (Brody et al, 2004), and chronic smoking leads to disruptions in the dopaminergic system including lower striatal dopamine D2 receptor availability (e.g., Albrecht et al, 2013; Wiers et al, 2017) and neural responses to the MID task (e.g., Fedota et al, 2015; Nestor et al, 2016). Whether smoking also influences SLC6A3 methylation, however, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the group differences in smoking may have influenced our results. That is, similarly to alcohol, smoking a cigarette increases dopamine release in the midbrain (Brody et al, 2004), and chronic smoking leads to disruptions in the dopaminergic system including lower striatal dopamine D2 receptor availability (e.g., Albrecht et al, 2013; Wiers et al, 2017) and neural responses to the MID task (e.g., Fedota et al, 2015; Nestor et al, 2016). Whether smoking also influences SLC6A3 methylation, however, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers showed more cue-related VMPFC activation during the satiated condition than nonsmokers during the placebo condition, although the hypothesized differences in striatal activation were not found. Previous studies that compared MID rewardrelated activation between smokers and nonsmokers have shown that smokers have less activation in the frontal cortex, 14,15 NAcc, 14,15 and caudate, 15 or more activation in the frontal cortex 16 and caudate. 14 Greater activation has been interpreted to represent stronger reward-related motivation or salience for nondrug rewards, which may be diminished in smokers, 14 or enhanced by nicotine exposure.…”
Section: Differences Between Smokers and Nonsmokersmentioning
confidence: 97%
“…The MID has been used to investigate the influence of addictive drugs on the neural response to the anticipation and receipt of nondrug rewards. 13 In particular, previous research has shown differences between smokers and nonsmokers, [14][15][16] as well as effects of nicotine and withdrawal 14,15 in reward-related brain activation. While this research demonstrates the sensitivity of the MID to nicotine manipulations, results have been inconsistent.…”
Section: Introductionmentioning
confidence: 97%
“…Placing these observations in the larger context of TUD, accumulating evidence links an extended smoking history with striatal hypoactivity during monetary-reward processing tasks [25, 55, 5761], albeit, not consistently [62, 63]. More severe striatal hypoactivity to aspects of monetary reward has been associated with poorer outcomes among smokers when considering the number of cigarettes smoked per day [64], craving severity [56], their ability to briefly refrain from smoking [59], and, ultimately, relapse rates [58].…”
Section: Toward Brain Network-level Biomakers Of Addiction Severitymentioning
confidence: 99%